A instrumentalização do Tribunal Constitucional por agentes políticos: um caminho para a erosão democrática - Silva , Thiago Viola Pereira da (2021)
Dissertation that investigates which instruments were used to undermine liberal democracy and which circumstances facilitated its degradation, assuming that one of the necessary phases for the perpetuation of autocratic regimes is the instrumentalization of constitutional courts. Initially, a sociological posture was adopted, whose theoretical basis is the notion of fields by Pierre Bourdieu, to understand how agents act and relate, dispute and accumulate legal and political capital, guided by predispositions that constitute his habitus. Then, bibliographical research and the Bourdieusian methodology was used to historically reconstruct the national legal-political field, having as focal point the power relations and the actions of the Federal Supreme Court. It demonstrates that the Constitutional Court, from its creation until the country's redemocratization, experienced a time of affirmation, in which several political acts aimed, many times successfully, to reduce its autonomy or instrumentalize it in favor of an authoritarian regime. Next, the Court's performance after the redemocratization is examined, in parallel with the phenomenon of democratic erosion, a period in which the judiciary established itself as one of the main protagonists of political clashes, reversing the concern for its independence to fear with its excesses. Despite the current scenario of consolidation of the independence of the Supreme Court, the empirical study of the Court with the comparative scenario demonstrates that countries in situations similar or analogous to the national regime had relatively consolidated democracies transformed into hybrid regimes or autocracies, a path followed from the instrumentalization of the respective Constitutional Courts, which were used to legitimize the acts of the anti-democratic regimes. It concludes, with the results achieved, that although isolated attacks are not sufficient, other mechanisms used together, in different contexts of history, including contemporaneously, should sound an alarm for autocratic incursions, as they are effective to undermine the independence of the Constitutional Courts